Diversity of freshwater shrimp species of the genus Macrobrachium (Decapoda: Caridea) in the big river of East Kalimantan, Indonesia - MAULIDA NUR ANNISA; KANTHI ARUM WIDAYATI; JUSMALDI JUSMALDI; ACHMAD FARAJALLAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Annisa MN, Widayati KA, Jusmaldi, Farajallah A. 2025. Diversity of freshwater shrimp species of the genus Macrobrachium (Decapoda: Caridea) in the big river of East Kalimantan, Indonesia. Biodiversitas 26: 1474-1484. Freshwater prawns are widely distributed in Indonesia, belonging to the subphylum Crustacea and order Decapoda. Freshwater shrimp commonly found in Indonesia belong to the families Atyidae and Palaemonidae. The Palaemonidae family is usually dominated by species of the genus Macrobrachium. Information on freshwater shrimp diversity in East Kalimantan, Indonesia, has never been reported, while water quality in East Kalimantan is declining due to increased exploitation of natural resources. This study was conducted to provide baseline information on freshwater shrimp species diversity for the future, before further changes occur in the East Kalimantan region and we provide Cytochrome Oxidase subunit I (COI) sequence data for molecular identification. Methods used for species identification based on morphological characters and species confirmation through molecular analysis using Cytochrome Oxidase subunit I (COI) gene fragments for molecular analysis. This study reports the diversity of freshwater shrimp in East Kalimantan, the results of morphological analysis showed confirmation of 7 species of freshwater shrimp. The family Palaemonidae consists of 7 species: Macrobrachium rosenbergii, M. lanchesteri, M. scabriculum, M. mammillodactylus, M. sintangense, M. equidens, and M. villosimanus. Molecular confirmation of species of the genus Macrobrachium using the COI gene showed genetic distance values ranging from 0 to 0.024. The species in this study have been confirmed based on genetic distance values and phylogenetic trees.